2013
DOI: 10.5009/gnl.2013.7.1.82
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Role of Acute Phase Reactants in the Response to Therapy in Patients with Chronic Hepatitis C Virus Infection

Abstract: Background/AimsBiochemical parameters and acute-phase proteins (APPs) may provide complementary data in patients with chronic hepatitis C (CHC). We aimed to evaluate the predictive role of APPs in the response to antiviral therapy.MethodsForty-five patients underwent antiviral therapy. Serum ferritin, C-reactive protein (CRP), transferrin, albumin, alpha-1 acid glycoprotein (A1AG), and alpha-2 macroglobulin (A2MG) levels were examined at the initial evaluation and at the 4th, 12th, and 48th weeks. HCV RNA leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 33 publications
2
9
0
Order By: Relevance
“…In a study of patients with angiographically documented CAD, CRP, and fibrinogen levels were significantly elevated in HCV‐infected patients compared to controls and HCV seropositivity was associated with increased severity of CAD . Similar results were reported with elevated high‐sensitivity CRP (hsCRP) levels and CVD in some studies, whereas others found no differences in CRP levels among HCV patients and controls …”
Section: Resultssupporting
confidence: 62%
See 3 more Smart Citations
“…In a study of patients with angiographically documented CAD, CRP, and fibrinogen levels were significantly elevated in HCV‐infected patients compared to controls and HCV seropositivity was associated with increased severity of CAD . Similar results were reported with elevated high‐sensitivity CRP (hsCRP) levels and CVD in some studies, whereas others found no differences in CRP levels among HCV patients and controls …”
Section: Resultssupporting
confidence: 62%
“…Numerous studies have reported decreased CVD clinical endpoints and mortality with HCV therapy . There were conflicting results about the change of these biomarkers in response to HCV treatment, and these differing results may have been due to heterogeneous study designs, variable study populations, and different treatment regimens among studies . Despite this variability, it was clear that eradication of HCV does have an effect on the HCV driven inflammatory and immune responses with a general trend towards return to normal levels of these markers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the context of acute-phase proteins, A2MG is synthesized in hepatocytes and stellate cells (11)(12). Both its hepatic and serum levels increase in fibrogenetic environment (13).…”
Section: Introductionmentioning
confidence: 99%